Assessing the performance of vision screening performed by trained teachers in school children - Kirag, Nukhet; Bilgen, Mehmet (Indian Journal of Child Health, 2018)
Background: The World Health Organization report states that visually impaired individuals around the world are as high as 285 million. Aim: This study aims to assess the validity of teacher-based vision screening in primary schoolchildren (aged 6–7 years), implemented post-training. Methods: The study was conducted between November 2014 and February 2015 in Aydin province of Turkey and it was planned in different phases; invitation of teachers for participation in the study, implementation of teacher training program for the screening of refractive error, strabismus and color blindness, and testing the teachers’ performance. Toevaluate the validity of the proposed teacher-based visual screening, the assessment results of the teachers were compared with the ophthalmologist’s diagnosis which was regarded as the gold standard. Results were expressed in terms of sensitivity, specificity, and positive and negative predictive values. Results: Eight teachers who successfully completed the training and participated in the student’s screening process, had teaching experience ranging from 5 to 15 years. The false positive error and false negative error rates were about 3% and 7%, respectively. Further, quantification yielded sensitivity of 84%, specificity of 94%, positive predictive value of 91%, and negative predictive value of 88%. Conclusions: Teachers with adequate training can accurately and reliably detect the refractive error, strabismus, and color blindness in schoolchildren.